THE INFLUENCE OF INTRINSIC AND EXTRINSIC FACTOR ON COMMITMENT AND THE IMPACT ON THE PERFORMANCE OF EMPLOYEES - Bodroastuti, Tri; Andhani, Aprillia Putri (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
This study aimed to determine the influence of intrinsic and extrinsic factors on commitment and impact on the performance of employees of Sejahtera Sunindo Trada Company. The populations in this study were employees of Sejahtera Sunindo Trada totaling 100 people. The entire population was sampled, so that the samples were 100 respondents. No sampling technique for this study since used census study which all employees which the workshop became respondents.The analytical tool used in this research was Structural Equation Model (SEM) using Partial Least Square (PLS). The first hypothesis testing showed there was no significant positive influnce between intrinsic factors and commitment by the t value was smaller than the value t table 1.274 < 1.96. The second hypothesis testing showed there was no with significant positive influnce between extrinsic factors with the commitment to the value of t is greater than t table is 1.973 > 1.96. The third hypothesis testing showed no significant positive influnce between commitment and performance and the intrinsic value of the t less than the value t table is 1.181 < 1.96. The fourth hypothesis showed there was no significant positive influence between intrinsic and performance with the value t was greater than t table 3.008 > 1.96. The fifth hypothesis was there no significant positive influence between extrinsic factors and performance by the t value greater than the value t table is 3.864 > 1.96.